A framework for managing the agri-fresh food supply chain quality in Indian industry. Issue 2 (24th December 2020) - Siddh, Man Mohan; Soni, Gunjan; Jain, Rakesh; Sharma, Milind Kumar; Yadav, Vinod
Abstract : Purpose: Research in agri-fresh food supply chain quality (AFSCQ) has been given less consideration in developing countries as compared to developed countries and its role in achieving organizational sustainability has not been researched yet. Thus, this study aims to determine and combine numerous significant factors to establish a framework for managing AFSCQ practices favorable to organizational sustainability in the Indian context. Design/methodology/approach: To accomplish this, all-inclusive framework of AFSCQ has been established through succeeding phases of data collection, analysis using structural equation modelling along with refinement of data. The collection of data for this study was from the Indian food industry, which relates to agri-fresh food products. Findings: The AFSCQ practices are conducive to enrich organizational sustainability, and then enhance economic, social and environmental performance indirectly. The study established relationships among the AFSCQ practices promising to enhance organizational sustainability. Originality/value: AFSCQ practices have a huge impact on organizational sustainability by means of practices that sum up activities along the whole supply chain. The organizational sustainability consists of economic, social and environmental sustainability.